HUBUNGAN ANTARA DERAJAT BERAT INFEKSI VIRUS DENGUE DAN KADAR NATRIUM SERUM - Agung Budiyasa, Dewa Gde; Parwati Merati, K Tuti (journal of internal medicine, 2011)
Dengue Viral (DV) infection has been a big problem on the world (WHO, 2005). One of the factors that can inß uencesuccesfull of the DV infection treatment was correction for hyponatremia as one of the factors caused dengue encephalopathy.Hyponatremia cause by plasma leakage, the more severe plasma leakage the more severe hyponatremia. The aim of this study toknow association between degree of severity of DV infection and natrium serum concentration, correlation between two signsof plasma leakage (albumin concentration and hematocrit) with serum natrium concentration. Analytic cross sectional designbe applied for DV infection patients who admitted at Internal Medicine Department of Sanglah General Hospital on November! December 2010. Pearson correlation test showed signiÞ cant correlation between albumin and serum natrium (p = 0.018, r =0.254), no signiÞ cant correlation between hematocrit and natrium serum (p = 0.861, r = 0.019). Linear regression showed pvalue for albumin 0.495 and degree of severity of DV infection 0.000, so variable that can predict natrium serum concentrationwas degree of severity of DV infection, stated with formula y = 134,515 - 2,664x. The conclusion we found there was negativeassociation between degree of severity of DV infection and natrium serum concentration which signiÞ cant between DF and DHF.But among degree of DHF there were just tendention that the more severe degree of severity of DHF the lower serum natriumconcentration. There was signiÞ cant correlation between albumin and natrium serum concentration, but albumin can